Identifying Potential Urban Greenways by Considering Green Space Exposure Levels and Maximizing Recreational Flows: A Case Study in Beijing’s Built-Up Areas - Tao Liu; Le Yu; Xin Chen; Yunmiao Chen; Xiaomeng Li; Xinyi Liu; Yue Cao; Fan Zhang; Chenggang Zhang; Peng Gong (Land)
Urban greenways are pivotal in enriching urban quality and fostering socio-ecological sustainability. Previous studies on urban greenway networks have often overlooked user-based experience efficiency, leading to the underutilization and insufficient translation of cultural services into human well-being. In this study, we introduce a user behavior-driven assessment framework for planning multifunctional urban greenways that connect parks with high green space exposure and maximize recreational mobility. Beijing’s built-up urban areas (BBUA) were selected as the case study area. Firstly, we evaluated the green space exposure of 331 parks in BBUA using an integrated “Availability–Accessibility–Adaptability” assessment framework as potential carriers. Then, through spatially explicit workflows and the least-cost path methodology, we leveraged a vast dataset of 70 million public transportation swipe records to optimize the alignment of multifunctional greenways, prioritizing the criterion of maximizing recreational footfalls. The results showed that the potential greenways network spans 1566.36 km in BBUA, encompassing 93.88% of parks and offering six diverse functions. It can serve 34.39–35.92% of bus recreation passengers, with this ratio tending to be higher on weekends. However, we identified obstacle points (non-greenway sections) in the networks based on residents’ view perceptions and panoramic street images, primarily located in densely built-up central areas and along southern trunk roads. By addressing these disconnections, the integrity and connectivity of urban greenway networks in BBUA will be improved. Overall, the framework we present can be used to construct greenway networks that maximize the perceived accessibility for bus-based visitors, with valuable implications for sustainable urban planning and regeneration initiatives.